Fate and Prognostication in the Chinese Literary Imagination - Lackner, Michael; Tam, Kwok-Kan; Gänßbauer, Monika; Siu Han Yip, Terry (Brill, 2020)
The essays collected in Fate and Prognostication in the Chinese Literary Imagination deal with the philosophical, psychological, gender and cultural issues in the Chinese conception of fate as represented in literary texts and films, with a focus placed on human efforts to solve the riddles of fate prediction. Viewed in this light, the collected essays unfold a meandering landscape of the popular imaginary in Chinese beliefs and customs. The chapters in this book represent concerted efforts in research originated from a project conducted at the International Consortium for Research in the Humanities at the Friedrich-Alexander-University Erlangen-Nuremberg, Germany. Contributors are Michael Lackner, Kwok-kan Tam, Monika Gaenssbauer, Terry Siu-han Yip, Xie Qun, Roland Altenburger, Jessica Tsui-yan Li, Kaby Wing-Sze Kung, Nicoletta Pesaro, Yan Xu-Lackner, and Anna Wing Bo Tso. <br